Hepatic arterial complications in adult living donor liver transplant recipients: a single‐center experience of 673 cases. (16th July 2014) - Iida, T.; Kaido, T.; Yagi, S.; Hori, T.; Uchida, Y.; Jobara, K.; Tanaka, H.; Sakamoto, S.; Kasahara, M.; Ogawa, K.; Ogura, Y.; Mori, A.; et al.
Abstract Background Hepatic arterial reconstruction during living donor liver transplantation (LDLT) is a very delicate and technically complicated procedure. Post‐LDLT hepatic arterial complications are associated with significant morbidity and mortality. Methods We retrospectively analyzed the details of post‐operative hepatic arterial complications in 673 consecutive adult LDLT recipients between January 1996 and September 2009. Results Hepatic arterial complications occurred in 43 of 673 adult recipients (6.4%) within a median of 13 post‐transplant days (range, 1–63). These included hepatic artery thrombosis (including anastomotic stenosis) in 33 cases, anastomotic bleeding in seven cases, and rupture of anastomotic aneurysm in three cases. To treat these complications, surgical re‐anastomosis was performed in 26 cases, while the other 17 cases underwent conservative therapies, including four angioplasties by interventional radiology. Biliary complications after hepatic arterial complications occurred in 17 cases. The overall survival rate after LDLT was significantly lower in the hepatic arterial complication group compared with that in the non‐complication group (60.7% vs. 80.1% at one yr, 44.3% vs. 74.2% at five yr, respectively; p < 0.001). Multivariate analysis showed that the extra‐anatomical anastomosis (p = 0.011) was the only independent risk factor for hepatic arterial complications. Conclusion Because hepatic arterial complications after LDLT are associated with poor patient survival, early diagnosis and immediate treatment are crucial. The anatomical anastomosis may be the first choice for the hepatic arterial reconstruction to the extent possible.